Direct Detection and Identification of the Most Common Bacteria and Fungi Causing Otitis Externa by a Stepwise Multiplex PCR - Aboutalebian, Shima; Ahmadikia, Kazem; Fakhim, Hamed; Chabavizadeh, Javaher; Okhovat, Ahmadreza; Nikaeen, Mahnaz; Mirhendi, Hossein (Frontiers in Cellular and Infection Microbiology, 2021)
Background Considering the importance of differential diagnosis of infectious otitis externa (OE), a stepwise PCR-based assay using universal and genus- or species-specific primers for the detection/identification of the most prevalent bacterial and fungal OE was developed and evaluated on the ear aspiration specimens of clinically suspected patients. Methods and Materials A total of 120 ear aspiration specimens with otomycosis suspicion were subjected to manual DNA extraction using phenol–chloroform extraction after tissue digestion with a lysis buffer. The multiplex PCR was initially performed using pan-fungal and bacterial homemade primers. Pseudomonas and Staphylococcus specific primers were simultaneously used in one reaction mixture to identify the bacterial genera. Furthermore, for the identification of fungal agents, Candida species-specific multiplex primers targeting the most clinically important Candida species causing OE (i.e., C. albicans, C. parapsilosis, and C. auris), as well as Aspergillus related multiplex PCR identifying the most prevalent Aspergillus species were used in two separate reaction mixtures. All the results of multiplex PCR were interpreted based on the amplicon size. Results The overall multiplex PCR-based detection rate of bacterial (n = 88; 73.3%) and fungal (n = 97; 81%) OE was documented to be 100% along with and complete consistency with the results of direct examination and Giemsa staining. Double amplicon bands of bacterial and fungal pathogens were evidenced in 76 specimens (63.3%). Moreover, the positivity rate of pan-fungal PCR was higher than that of the culture result. Out of 88 pan-bacterial positive PCR specimens, 66 and 47 ones were positive for Staphylococcus and Pseudomonas, respectively. In addition, 30 samples exhibited mixed infection of both, and five specimens remained negative. Out of 97 pan-fungal positive PCR specimens, 67 and 51 ones contained Candida and Aspergillus species, respectively. It should be noted that dual amplicon bands of Candida and Aspergillus-related multiplex PCR were yielded in 30 specimens. Conclusion The stepwise multiplex PCR assay proved to be more sensitive, more rapid, as well as less cumbersome in detection and identification of fungal and bacterial OE, compared to culture.